Micropatterning of electrochemiluminescent polymers based on multipolar Ru-complex two-photon initiators - Mhanna, Rana; Durand, Nicolas; Savel, Paul; Akdas-Kilic, Huriye; Abdallah, Stephania; Versace, Davy-Louis; Soppera, Olivier; Fillaut, Jean-Luc; Sojic, Neso; Malval, Jean-Pierre (ROYAL SOC CHEMISTRY, 2022)
In this work, we present an original stereolithography strategy based on multibranched Ru-complexes with a high two-photon initiating ability allowing the 'one-pot' direct laser writing of ECL-active materials deposited onto electro-active surfaces at the mu m scale.
Keywords: EFFICIENT; ELECTRON; DONOR; Chemistry